Fermented soybean meal enhances soil health, rhizosphere microenvironment and tea quality via microbial and metabolite changes - Huan Wang; Yujie Song; Litao Sun; Kai Fan; Wenmei Wang; Yu Wang; Zhaotang Ding (Food Chemistry: X, 2025)
Fermented soybean meal (FSBM) is a promising organic fertiliser that enhances soil fertility and improves tea quality. This study investigated the dynamic changes in FSBM metabolites and microorganisms, as well as their effects on potted tea plants. After fermentation, FSBM exhibited significant increases in total phosphorus, copper, zinc and manganese contents, along with marked accumulations of amino acids and short-chain fatty acids, and enrichment of beneficial microorganisms such as Pseudomonas and Bacillus. FSBM application enhanced soil organic matter, total nitrogen, available nitrogen and available phosphorus contents by 39.64 %, 26.24 %, 33.67 % and 28.59 %, respectively, and increased soil urease and catalase activities. It promoted the growth of beneficial rhizosphere microorganisms and significantly increased the amino acid and volatile compound contents in tea shoots. These results underscore the potential of FSBM to improve soil health and enhance tea quality, supporting its application as an effective organic fertiliser.